PERUBAHAN BUDAYA PRA-NIKAH ETNIK BATAK TOBA DI DESA SAITNIHUTA - Simamora, Bilferi; Rumapea, Murni Eva (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
The development of science, technology and the introduction of religion into Indonesia has led to socio-cultural changes in society. This study aims to determine the changes that occur in Toba Batak customs due to the influence of Christian teachings in the village of Saitnihuta. This study uses a qualitative research method with a descriptive approach. Collecting data in this study are interviews, observation and documentation. The results of this study indicate that there are several pre-marital cultures that have been forgotten and are no longer practiced in Saitnihuta village, such as Mamele Sahala Ni Ompu and Maniti Ari. The changes that have occurred due to the development of science, technology and Christianity are not only in the pre-marriage of the Toba Batak ethnic group, but in many other cultures. However, this article will only discuss in detail the changes in pre-marital marriages of the Toba Batak ethnicity in the village of Saitnihuta.